Empire and Order: The Gospel and Same-Gender Relationships - Johnson, William Stacy (2007)
The handful of New Testament passages addressing homoeroticism need to be read within the wider contexts of conquest, dominance and submission that characterized the world of the Roman empire. In particular, the sexual indignities visited upon slaves provide an illuminating window into the ethical concerns of the early Christian community. That despite these indignities being a slave could became the chief way of defining life in Christ shows just how radical the Christian vision of redemption is. Embodying such a redemption requires Christian communities to draw upon every source they can—biblical, legal, and otherwise—to craft a welcoming and affirming stance toward gay and lesbian people, both as individuals and as committed couples.